Ethical Considerations and Analysis in Relation to Photography - Alfaro López, Héctor Guillermo (Revista General de Información y Documentación, 2019)
Right from its invention, the origin of photography was linked to a commercial context.Right from its invention, the origin of photography was linked to a commercial context.This explains that its professionalization has also been based on economic grounds. In this way, thephotographer and his/ her camera became simply a means to obtain economic profits through his/herphotos. Such perspective fostered the dehumanization of photography. An alternative perspective tothis situation points out the possibility of endowing photography with an ethical underpinning.Kantian ethics constitute a moral basis where human beings are considered not only as a means, butalso as an end in itself. In this way, both humanity and human actions recover their dignity. From thispoint of view derives the formula: the photographic act is a moral act. In these terms, thephotographer and his/her camera involve a human purpose, they are not simply a means with afinancial aim. This consideration puts forth a path gives which endows the photographic professionwith an ethical support.
Keywords: Ethics; Morals; Photography; Photographic act; Moral act; Utopia